2005
DOI: 10.1302/0301-620x.87b2.15055
|View full text |Cite
|
Sign up to set email alerts
|

The effect of psychological disturbance on symptoms, self-reported disability and surgical outcome in carpal tunnel syndrome

Abstract: In a prospective study, we have evaluated the impact of psychological disturbance on symptoms, self-reported disability and the surgical outcome in a series of 110 patients with carpal tunnel syndrome. Self-reported severity of symptoms and disability were assessed using the patient evaluation measure and the Boston carpal tunnel questionnaire. Psychological distress was assessed using the hospital anxiety and depression scale. There was a significant association between psychological disturbance and the pre-o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
27
1
1

Year Published

2008
2008
2016
2016

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 40 publications
(29 citation statements)
references
References 43 publications
0
27
1
1
Order By: Relevance
“…20 Other studies have also reported the relationship of CTS with depression. 21,22 In our study, the Beck depression scores of CTS patients were higher than those of the control group. We found that the income level of patients with CTS was lower than that of the control group.…”
Section: Discussioncontrasting
confidence: 42%
“…20 Other studies have also reported the relationship of CTS with depression. 21,22 In our study, the Beck depression scores of CTS patients were higher than those of the control group. We found that the income level of patients with CTS was lower than that of the control group.…”
Section: Discussioncontrasting
confidence: 42%
“…26 However, other studies performed on patients with whiplash 33,48 and neck pain 42 did not find a link between age and disability. We also did not find age to be related to the CTS-related level of disability.…”
Section: Discussionmentioning
confidence: 94%
“…15 Deficiencies in sensory and motor processes often result in alteration in force adaptations, which can lead to the inability to adequately perform functional activities with the upper limb. 1 Patients with CTS exhibit physical and psychological 25 impairments before surgical intervention. It has been reported that women with CTS exhibit restricted cervical range of motion (ROM) in flexion, extension, and lateral flexion compared to healthy people.…”
Section: T T Backgroundmentioning
confidence: 99%
“…It consists of 2 scales that evaluate symptoms (BCTQ-S) and function (BCTQ-F). 10 The first scale consists of 11 questions that address the severity and frequency of pain, numbness, weakness, and loss of dexterity. Each of the multiple choice questions offers 5 possible responses of increasing severity, and responses are scored from 1 (no symptoms) to 5 (severe symptoms).…”
Section: Methodsmentioning
confidence: 99%
“…The BCTQ has been formally validated 7,12 and been shown to be more sensitive than other outcome measures in CTS. 10,12 The CES-D was designed to measure current level of depressive symptoms. The 20 items on the questionnaire are used to measure the various aspects of depression, and each item is scored using a 4-point scale (0 to 3 [greatest depression]).…”
Section: Methodsmentioning
confidence: 99%